Plant stem cells: unity and diversity - I. E. Dodueva; V. E. Tvorogova; M. Azarakhsh; M. A. Lebedeva; L. A. Lutova (Вавиловский журнал генетики и селекции, 2016)
Stem cells are undifferentiated cells of multicellular organisms that can divide, self-renew and differentiate. Despite the differences of properties, general principles of the existence of stem cells can be distinguished in all multicellular organisms. In plants, stem cells are found in meristems – the structures that ensure the continuous growth of plant and provide material for the formation of various specialized tissues. There are numerous types of meristems: shoot and root apical meristems, lateral meristems (procambium, cambium, pericycle), as well as the so-called irregular meristems, developing under certain conditions (callus, meristems of symbiotic nodules, spontaneous and pathogen-induced tumors, etc.). For each of meristems, specific mechanisms of regulation, which are based on the interaction of plant hormones and the major groups of transcription factors, were identified. The activity of meristems is based on two opposite processes: proliferation and self-renewal of stem cells in the central part of the meristem and differentiation of specialized cells in the periphery. WOX-CLAVATA systems are a regulatory component conservative for different meristems and providing consistency of the composition of the meristem, as well as the balance of stem cell proliferation and differentiation. In this review, we will consider the similarities and differences between the principles of organization of stem cell niches in plants and animals, as well as in a variety of meristems of higher plants; special attention will be paid to the role of WOX-CLAVATA systems in maintaining meristems and their interaction with other meristem regulators.